On the Natural Blood Coagulation Inhibitor System Investigations of Inhibitor Factors Based on Antithrombin Deficient Blood - Egeberg, O (Thrombosis and Haemostasis, 1965)
Natural coagulation inhibitor factors were studied in sera, or in fractions of sera, from patients with congenital partial deficiency of antithrombin and from normal persons. In the patients’ sera the progressive antithrombin (antithrombin III) and heparin cofactor (antithrombin II) had both been measured around 50 per cent of normal level.No decreased activity could be demonstrated in the patients’ sera as to antiprothrombinase, the inhibitor against blood intrinsic prothrombinase activity.For anticonvertin, the inhibitor against the tissue convertin complex, the activity was found decreased to about the same level as that demonstrated for antithrombin III and II. The results lend strong support to the hypothesis that the activities measured as anticonvertin, antithrombin III and antithrombin II represent functions of the same blood protein, which on the other side appears to be distinct from antiprothrombinase. In accordance with this explanation, an antithrombin III concentrate had also antithrombin II and anticonvertin activity, and further, adsorption of a normal human serum with convertin appeared to specifically reduce its antithrombin III activity.The inhibitor against activated antihemophilic C factor (AHC’ = activated f. XI) was studied in sera adsorbed with BaS04 and celite. The inhibitor activity was found at normal level in the patients’ sera, consistent with the view that anti-AHC’ is distinct from antithrombin III, II and from anticonvertin. No acceleration of the anti-AHC’ activity could be demonstrated after addition to the inhibition mixture of weak solutions of heparin.The results are discussed.